Humanoid robot simulator: a realistic dynamics approach - Lima, José (2010)
This paper describes a humanoid robot simulator with realistic dynamics. As simulation is a powerful tool for speeding up the control software development, the suggested accurate simulator allows to accomplish this goal. The simulator, based on the Open Dynamics Engine and GLScene graphics library, provides instant visual feedback and allows the user to test any control strategy without damaging the real robot in the early stages of the development. The proposed simulator also captures some characteristics of the environment that are important and allows to test controllers without access to the real hardware. Experimental results are shown that validate this approach.